Eating and Control Styles Axis in Mentalisation-Based Psychotherapy in Eating Disorders: A Randomised Clinical Trial - Golan, Moria (Frontiers in Psychiatry, 2022)
Background: Clinicians need an instrument that helps their patients with eating disorders (ED) to explore their agent's inner intentions and confront negative behaviour and control styles. Objectives: To assess the feasibility and impact of an eating and control styles axis (ECOSA) during the first eight months of mentalisation-based psychotherapy with a community-based sample of Ed patients. Methods: Six experienced therapists and their consecutively admitted patients were randomly allocated to the intervention and control groups. A total of 94 women, Mage= 24 were recruited between June 2020 and October 2021. Ninety completed it. Both groups received mentalisation-based psychotherapy, but only the intervention group used the ECOSA repeatedly. Therapists and participants were blinded to the study aims and hypothesis. Fidelity assessment was applied to ensure that the two groups differed mainly in terms of ECOSA usage. Results: The use of ECOSA, although less than advised, was reported as feasible. The effect size of the improvement in reflective functioning was larger than that of the control group and correlated significantly only in the intervention group with EDE-Q score (r=0.46; p=0.001). Conclusions: Although the study limitations: selective population, relatively small sample size and the lack of controlled confounder, the combined quantitative and qualitative results lend preliminary evidence for the validity and contribution of ECOSA as a possible instrument that may upgrade the clinician’s toolbox in the treatment of ED. A more rigorous study design is needed to explore the potential usage of ECOSA as a clinical tool to enhance mentalisation among people with ED